Sitting posture detection and recognition using force sensor - Yong-Ren Huang; Xu-Feng Ouyang (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
This paper presents an architecture for information capture and analysis of sitting posture using force sensor. We utilize force sensor and microcontroller to build a system for force information. We fix positions of force sensors on seat cushions firstly. Then, we design the circuits on microcontroller and obtain the data from sensors. There are different types of information in deferent sitting postures. We analyze and categorize the information for recognizing the sitting postures. This system could be utilized to detect the incorrect sitting postures for children, patients or elder people in the future.